Różnorodność paradygmatów dydaktyki akademickiej. O potrzebie komplementarności podejść - Sajdak-Burska, Anna (Kultura-Społeczeństwo-Edukacja, 2018)
This paper concerns itself with the interdisciplinary nature of academic didactics as a field of social sciences that uses knowledge and results derived from educational sciences, psychology, philosophy, sociology and didactics specific to particular subjects. It was pointed out that considerations on teaching practices in all scientific disciplines constitute another source of knowledge for the field of academic didactics. The diversity of theoretical and methodological approaches is determined by science-specific and discipline- specific research methodology paradigms, diversified teaching cultures dependent on environmental conditions as well as diversified teaching class patters for students that are often specific to an educational profile. The issue addressed in this paper is whether a single didactic paradigm exists that would unify approaches so different in terms of theory and practice. The paper provides a map of academic didactics paradigms, a description of difficulties related to paradigmatic translations as well as the lack of consent to the multiparadigm approach and issues with interferences and shifts between paradigms. Despite the existing difficulties, the suggestion is made to promote the complementary attitude to various approaches. It is supported by the concept of relations between the assumed academic didactics effects and teaching strategies that lead thereto, which are constituted by different teaching and learning patterns.